2019
DOI: 10.1039/c9ra04499j
|View full text |Cite
|
Sign up to set email alerts
|

Ligand geometry controlling Zn-MOF partial structures for their catalytic performance in Knoevenagel condensation

Abstract: Novel 1D to 3D structures of Zn-MOFs and their morphologies were assembled and showed high catalytic performance for Knoevenagel condensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, as shown in entries 1 and 2, the unsatisfactory results obtained by employing single NUC-30 or n -Bu 4 NBr demonstrated that the active open metal sites of NUC-30 and anions of Br − played different roles during the cycloaddition reaction of CO 2 and epoxides. Therefore, the optimal reaction conditions used for subsequent experiments were quantified as 1.0 mol% NUC-30 catalyst, 5 mol% n -Bu 4 NBr co-catalyst, and 1.0 MPa CO 2 at 60 °C for 8 h. Compared with the recently reported MOF-based catalysts, 20 NUC-30 showed a superior catalytic performance in terms of reaction conditions (Table S4 † ), which should be attributed to its intrinsic characteristics of active metal sites (Zn II and Ho III ), uncoordinated pyridine and carboxyl oxygen atoms, and unimpeded void space. Furthermore, besides the synergistic catalytic effect of NUC-30 and n -Bu 4 NBr, the reaction temperature plays a key role during the cycloaddition process.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, as shown in entries 1 and 2, the unsatisfactory results obtained by employing single NUC-30 or n -Bu 4 NBr demonstrated that the active open metal sites of NUC-30 and anions of Br − played different roles during the cycloaddition reaction of CO 2 and epoxides. Therefore, the optimal reaction conditions used for subsequent experiments were quantified as 1.0 mol% NUC-30 catalyst, 5 mol% n -Bu 4 NBr co-catalyst, and 1.0 MPa CO 2 at 60 °C for 8 h. Compared with the recently reported MOF-based catalysts, 20 NUC-30 showed a superior catalytic performance in terms of reaction conditions (Table S4 † ), which should be attributed to its intrinsic characteristics of active metal sites (Zn II and Ho III ), uncoordinated pyridine and carboxyl oxygen atoms, and unimpeded void space. Furthermore, besides the synergistic catalytic effect of NUC-30 and n -Bu 4 NBr, the reaction temperature plays a key role during the cycloaddition process.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the absence of a clear linkage of catalyst structure with its activity, a better performance of 1, 2, and 4 can be associated with their one-dimensional structures and the presence of open metal sites (Lewis acid sites) or labile H 2 O ligands. 42,[54][55][56] In fact, these catalysts may display zinc(II) centers that are more accessible for catalytic action in comparison to 3 and 5 that are 2D and 3D coordination polymers, respectively. These factors may potentially explain an enhanced catalytic activity of CPs 1, 2, and 4 in the Knoevenagel condensation reaction that follows a common mechanism described for other coordination polymer catalysts.…”
Section: Emission Propertiesmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) frequently recognized as porous coordination polymers (PCPs) are materials with excellent crystallinity composed of metal ions/metal clusters with organic linkers. Switchable MOFs are a type of smart materials that undergo distinct and reversible structural changes upon exposure to the external stimuli, thus finding interesting technological application . The geometry of a ligand governs crystal topology of MOFs and tunes micro-to-nano crystal morphologies . For instance, the ZIF-MOF family offers excellent chemical and thermal stability and adjustable porous structures .…”
Section: Introductionmentioning
confidence: 99%
“…7 The geometry of a ligand governs crystal topology of MOFs and tunes micro-to-nano crystal morphologies. 8 For instance, the ZIF-MOF family offers excellent chemical and thermal stability and adjustable porous structures. 9 Over past couple of decades, PCPs have drawn tremendous attention and established prodigious worldwide interest not only owing to versatile designability, excellent tunable porosity, structural diversity, miscellaneous topologies, and high surface areas but also due to their fascinating applications in waste water treatment, 10−13 catalysis and gas storage/separation, 14−17 chemical sensing, 18−20 optoelectronic materials, 21−26 heterogeneous catalysis, 27−34 water oxidation, 35,36 energy storage and conversion, 37−40 luminescent materials, 41−44 and so forth.…”
Section: Introductionmentioning
confidence: 99%